The Dynamics of Coral-Algal Interactions in Space and Time on the Southern Great Barrier Reef - Brown, Kristen T.; Bender-Champ, Dorothea; Kubicek, Andreas; van der Zande, Rene; Achlatis, Michelle; Hoegh-Guldberg, Ove; Dove, Sophie G. (Frontiers in Marine Science, 2018)
Globally, tropical coral reefs are being degraded by human activities, and as a result, reef-building corals have declined while macroalgae have increased. Recent work has focused on measuring macroalgal abundance in response to anthropogenic stressors. To accurately evaluate the effects of human impacts, however, it is necessary to understand the effects of natural processes on reef condition. To better understand how coral reef communities are influenced by natural processes, we investigated how spatial and seasonal changes in environmental conditions (temperature and PAR) influence benthic community structure, and the composition and frequency of coral-algal interactions across 8 distinct zones and over a 23-month period at Heron reef on the southern Great Barrier Reef. Hard coral cover and macroalgal density showed distinct spatio-temporal variations, both within and between zones. Broad hard coral cover was significantly higher at the reef slope sites compared to the lagoon and was not significantly influenced by season. The composition and biomass of macroalgae increased in spring and declined in summer, with maximum macroalgal abundance corresponding with average temperatures of between 22-24°C and average 24h PAR of 300-500 µmol qanta m-2 s-1. Changes in macroalgal biomass further influenced the composition and frequency of coral-algal interactions, however the incidence of coral-algal contact was best explained by coral cover. The results presented here emphasize that natural levels of macroalgae and coral-algal interactions are context -specific, and vary not only with-in zones, but in somewhat predictable seasonal cycles. Further, these results emphasize that the frequency of coral-algal interactions is dependent on hard coral, not just macroalgal cover, and an increase in coral-algal interactions does not necessarily translate to degradation of coral reefs.